PEMBERDAYAAN IBU BALITA MELALUI EDUKASI STUNTING DAN DIVERSIFIKASI PANGAN JAGUNG: STUDI KASUS DESA BONTO BUNGA KECAMATAN MONCONGLOE KABUPATEN MAROS - Baharuddin, Nurul Hikmah; Asis, Muhammad Arfah; Islamiah, Nurhidayati (Universitas Mataram, 2025)
Stunting is a national priority issue today. Consumption of nutritious food and the Closed Mouth Movement (GTM), a condition where children refuse to open their mouths while eating, are factors that impact weight gain in children and children are more likely to experience malnutrition. The purpose of this activity is to increase mothers' awareness of the importance of nutrition in toddlers by providing education on nutrition and stunting, tricks for handling GTM children, education on parenting and mothers' thinking patterns regarding food myths, assistance in making local corn-based food and forming BUSI (Nutrition Aware Mothers) groups that can share knowledge with mothers about child nutrition issues. This activity method uses community development with 4 (four) stages of implementation. This activity was carried out in Bonto Bunga Village, Moncongloe District, Maros Regency. The results of this activity showed that participants were enthusiastic about participating in the education activities and demonstrations of local corn-based food processing. Overall, the education and demonstrations carried out in this community service activity are important strategies that require sustainability so that the community, especially mothers with toddlers, understand stunting, its impacts and dangers in the future to improve public health and overcome the burden of malnutrition on the nation's future generations.